Attitudes of Arab university students and general public towards people who stutter. (December 2014) - Abdalla, Fauzia; Irani, Farzan; Hughes, Stephanie
Abstract : Speech-language pathology is a burgeoning field in many Arab countries, including Kuwait. While a small number of studies have investigated Kuwaiti attitudes toward stuttering and people who stutter (PWS), no such studies have been conducted with a broad sampling of the general public. In this study, a modified version of Bebout and Arthur's (1992) questionnaire to measure attitudes toward communication disorders was adapted into Arabic and administered to 943 university students and adult members of the general population living in Kuwait. Results indicated that attitudes toward stuttering and PWS in Kuwait are generally positive, though negative trends were observed for some items related to the perceived causes and traits of stuttering as well as vocational/societal inclusion of PWS. The findings indicate that members of the general public in Kuwait and other Arab countries could benefit from increased knowledge of stuttering and how to interact with PWS. Speech-language pathologists and PWS who conduct public awareness campaigns in these countries may find it prudent to adopt educational strategies, which are specific to their target populations.